Efektivitas Bumdes Sejahtera Bersama Dalam Meningkatkan Kesejahteraan Peternak Kambing brabados di masa pandemi Covid 19 di Desa Lawe loning Aman Kecamatan Lawe Sigalagala Kabupaten aceh tenggara - Yunita Althin Natanael; Ardi Hirmansyah (Jurnal Riset AKuntansi dan Bisnis, 2022)
This research aims to determine the effectiveness of the performance of Village Owned Enterprises (BUMDes) in improving community welfare. The method used in this study is to use qualitative data analysis techniques, in which the author only describes the problem as it is or in accordance with the reality that occurs in the object of research. The results of this study indicate that BUMDes in the village of Lawe Loning Aman, Lawe Sigalagala District, Southeast Aceh Regency shows that it is still not effective, seen from the three BUMDes principles that are applied in three of the seven elements of effectiveness, where the element of growth effectiveness is seen in the application of participatory principles which is a It is important for us to pay attention to realizing a business that runs voluntarily, not to hesitate in increasing the contribution to the business group that is run so that the effectiveness of village-owned enterprises (BUMDes) with good growth and a participatory workforce so as to create better results.